2009
DOI: 10.1007/s11258-009-9572-9
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant composition of forest layers: the importance of environmental conditions and spatial configuration

Abstract: The species-environment relationships for woody species may vary according to the forest layers considered. In fragmented forest, spatial configuration may also influence forest layer composition. We investigated the relationships between four forest layer compositions and environmental conditions, and spatial variables accounting for forest fragmentation, in 59 forest stands. Field and shrub layer compositions were mainly linked to environmental conditions, particularly to soil pH and slope aspect, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
3
11
0
2
Order By: Relevance
“…Godefroid & Koedam (2003) found no forest species occurring only in the interior zone they studied, located at least 1 km from an urban area. Our results were in accordance with the findings of Gonzalez et al (2009) andHonnay et al (2002): Fagus sylvatica, Carpinus betulus, Quercus petraea and Convallaria majalis were also identified as core species in these studies whereas Fraxinus excelsior, Quercus robur, Galium aparine, Hedera helix, Sambucus nigra and Urtica dioica displayed edge profile. However, our results point to a much higher distance of correlation than those detected in the previous studies.…”
Section: Predictorsupporting
confidence: 92%
See 2 more Smart Citations
“…Godefroid & Koedam (2003) found no forest species occurring only in the interior zone they studied, located at least 1 km from an urban area. Our results were in accordance with the findings of Gonzalez et al (2009) andHonnay et al (2002): Fagus sylvatica, Carpinus betulus, Quercus petraea and Convallaria majalis were also identified as core species in these studies whereas Fraxinus excelsior, Quercus robur, Galium aparine, Hedera helix, Sambucus nigra and Urtica dioica displayed edge profile. However, our results point to a much higher distance of correlation than those detected in the previous studies.…”
Section: Predictorsupporting
confidence: 92%
“…Many studies have quantified a depth-of-edge influence (DEI), operating over the distance from the edge to the adjacent habitat where there is a tangible edge influence (Harper et al 2005). Depending on the variables considered (biotic or abiotic), this edge influence can extend into the forest for just a few metres or for as much as several hundred metres (Murcia 1995;Honnay et al 2002;Harper et al 2005;Gignac & Dale 2007;Gonzalez et al 2009Gonzalez et al , 2010. Forest edges have generally higher plant species richness (Ranney et al 1981;Fraver 1994;Gonzalez et al 2010), and higher shrub richness and cover (Matlack 1994a;Gignac & Dale 2007), than the forest interior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more shaded conditions, seedlings and suckers can be out-competed by more competitive species such as oak and beech (Schr€ otter 2001;Hochbichler 2003;Geb, Schmidt & Meyer 2004), but in less highly shaded conditions, they will persist as a sapling bank from 10 to 20 years of age or as mature trees, showing little annual growth or reproduction until a canopy gap opens up (Kausch-Blecken von Schmeling 1994b;Prudi c 1997;St anescu, S ßofletea & Popescu 1997;Hochbichler 2003;Kahle 2004;Rich et al 2010). As such, it is rarely a canopy tree in cool western areas of Europe; for example, in mixed oak woodlands in south-west France, S. torminalis occurred in 37-54% of 400 m 2 plots as an understorey shrub, and only 7% of plots as a canopy tree (Gonzalez, Deconchat & Balent 2009). In a Quercus petraea woodland in south-west Germany, Pyttel, Kunz & Bauhus (2013) found that 65% of S. torminalis trees were <7 cm DBH, and most were <10 m tall with only occasional trees >20 m and so shorter than the oaks.…”
Section: ( B ) P E R F O R M a N C E I N V A R I O U S H A B I T A T Smentioning
confidence: 99%
“…The scale at which the study is carried out is one of the most important factors when analysing species, richness and 2 International Journal of Biodiversity diversity changes as the variables impacting the species in a given area at a given scale might not be as important when analysed at a different scale [12,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%